Cellular Immunity in Mice Vaccinated with Recombinant Phospholipase D Toxoid of Hemiscorpius lepturus Scorpion - Narges Safari-Foroushani; Mohammad Hossein Modarressi; Kamran Pooshang Bagheri; Mahdi Behdani; Delavar Shahbazzadeh (Journal of Arthropod-Borne Diseases, 2022)
Background: Hemiscorpius lepturus is one of the most dangerous scorpions in Iran and the world. Numerous studies have been conducted on phospholipases, especially phospholipase D, in this scorpion’s venom, and the results have shown this protein to be the main cause of death. Therefore, one of the most effective ways of preventing fatalities is to produce a toxoid vaccine from the deadly toxin of the venom. The present study was conducted to assess the non-toxicity of this toxoid and the safety of the vaccine candidate in BALB/c mice.